Contrast‐enhanced CT and liver surface nodularity for the diagnosis of porto‐sinusoidal vascular disorder: A case‐control study. Issue 2 (16th February 2022) - Valainathan, Shantha Ram; Sartoris, Riccardo; Elkrief, Laure; Magaz, Marta; Betancourt, Fabian; Pellegrino, Silvia; Nivolli, Arianna; Dioguardi Burgio, Marco; Flattet, Yves; Terraz, Sylvain; Drilhon, Nicolas; Lazareth, Marie; et al.
Abstract: Background and Aims: Porto‐sinusoidal vascular disorder (PSVD) is a rare and commonly overlooked cause of portal hypertension. The interest of CT analysis, including quantification of liver surface nodularity (LSN) for PSVD diagnosis has not been established. This study aimed at assessing the performance of LSN and CT features for a PSVD diagnosis in patients with signs of portal hypertension. Approach and Results: This retrospective case‐control study included a learning cohort consisting of 50 patients with histologically proven PSVD, according to VALDIG criteria, and 100 control patients with histologically proven cirrhosis, matched on ascites. All patients and controls had at least one sign of portal hypertension and CT available within 1 year of liver biopsy. Principal component analysis of CT features separated patients with PSVD from patients with cirrhosis. Patients with PSVD had lower median LSN than those with cirrhosis (2.4 vs. 3.1, p  < 0.001). Multivariate analysis identified LSN < 2.5 and normal‐sized or enlarged segment IV as independently associated with PSVD. Combination of these two features had a specificity of 90% for PSVD and a diagnostic accuracy of 84%. Even better results were obtained in an independent multicenter validation cohort including 53 patients with PSVD and 106 control patients with cirrhosis (specificity 94%, diagnostic accuracy 87%). Conclusions: This study that included a total of 103 patients with PSVD and 206 patients with cirrhosis demonstrates that LSN < 2.5 combined with normal‐sized or enlarged segment IV strongly suggests PSVD in patients with signs of portal hypertension. Abstract : image